Acidity of Monsoon Rain Water - MUKHERJEE, ASOKE KUMAR (MAUSAM, 1964)
pH of rain water from continuous rains at Calcutta and Bombay were studied, It is found that the pH values lie within 6 and 7 pH of neutral rain water in monsoon is close to but less than.7.0. Thus it dissolves little carbon, dioxide whereas studies in Europe show that dissolved carbon dioxide In rain water is probably in equilibrium with the atmospheric carbon dioxide. This difference may be due to difference in mechanism of precipitation in two places.